Risk Analysis and Work Instruction for Accident Reduction in a Steel Structure contractor - Phookanngam, Pennapa (Journal of Vongchavalitkul university, 2023)
Objective: The objective of this research and development analytical study was to conduct a risk analysis, develop work instructions, and determine personal protective equipment. Additionally, it aimed to compare the Injury Frequency Rate (IFR), Injury Severity Rate or (ISR), and Safe-T-Score (STS) of current performance with the past performance of a steel structure contractor in Ayutthaya province. Methods: The research focused on three areas: Assembling, Welding and Painting. The data were analyzed using descriptive statistics. The study was conducted from July 2022 to February 2023. Results: The analysis of the accident statistics revealed a significant reduction in occurrence and severity compared to previous works. The Injury Frequency Rate or (IFR) for Assembling decreased to 1.75, while the IFR for Welding decreased to 0.00. The Injury Frequency Rate (IFR) of Painting decreases to 0.00. Similarly, the Injury Severity Rate (ISR) for Assembling decreased to 8.77. The Injury Severity Rate (ISR) for Welding and Painting decreased to 0.00. Comparing the current performance to the past performance, the Safe-T-Score (STS) for Assembling work was -2.53, for Welding work, it was -2.12, and for Painting work, it was -1.00. These results indicated a significant improvement in accident reduction compared to the past. The statistical analysis demonstrated the effectiveness of safety measures in reducing the frequency and severity of the accidents.